AUTOIMMUNE POLYGLANDULAR SYNDROME TYPE IIIA WITH LUPUS NEPHRITIS: A CASE REPORT - Lim, Hui Zhi; Lau, Simran; Ng, Ooi Chuan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Autoimmune polyglandular syndrome (APS) is a rare disorder characterized by multiple autoimmune endocrinopathies. The condition is driven by T-lymphocyte-mediated and autoantibody-induced destruction of various organs. APS Type III is defined by the presence of autoimmune thyroid disease in association with other autoimmune conditions, excluding adrenal insufficiency. APS Type IIIA specifically involves autoimmune thyroid disease and type 1 diabetes mellitus (T1DM). Early recognition and multidisciplinary management are crucial for optimal outcomes. CASE A 25-year-old Malay female with T1DM since age seven, inactive Graves’ disease, and systemic lupus erythematosus (SLE) with lupus nephritis presented with loose stools (Bristol 7), vomiting, heartburn, bloating, reduced oral intake, and oliguria of eight days duration. Though she was ambulatory, she had a 2-day history of generalized muscle weakness. There was no fever or other indicators of infection. No dietary indiscretion was noted. Type 1 diabetes mellitus was well-controlled on an insulin regimen. She had hypertension and dyslipidemia since age ten. Graves’ disease resolved three years ago after carbimazole treatment. Systemic lupus erythematosus was complicated by class IV/V lupus nephritis, initially treated with corticosteroids and cyclophosphamide, then eventually shifted to mycophenolate mofetil and bisphosphonates as maintenance therapy. Renal function corresponds to CKD stage 3 (eGFR 36 mL/min/1.73 m²). Examination revealed central obesity, bilateral pitting edema, and striae, without overt dehydration or hyperglycemia. No anemia, acute infection, cardiac failure, or thyroid dysfunction was noted. On the basis of the presence of T1DM, autoimmune thyroid disease, and SLE, she meets APS Type IIIA criteria. CONCLUSION This case highlights the need for heightened awareness of autoimmune polyglandular syndrome (APS), particularly APS Type IIIA, in patients presenting with multiple autoimmune endocrinopathies. Clinicians should maintain a high index of suspicion for APS in individuals with a history of multiple autoimmune disorders, allowing for early screening and intervention to prevent complications. Comprehensive autoimmune surveillance and interdisciplinary collaboration are essential for optimizing patient outcomes.